Asteroid electrostatic instrumentation and modelling - Aplin, K; Bowles, N; Urbak, E; Keane, D; Sawyer, E (2011)
Asteroid surface material is expected to become photoelectrically charged, and is likely to be transported through electrostatic levitation. Understanding any movement of the surface material is relevant to proposed space missions to return samples to Earth for detailed isotopic analysis. Motivated by preparations for the Marco Polo sample return mission, we present electrostatic modelling for a real asteroid, Itokawa, for which detailed shape information is available, and verify that charging effects are likely to be significant at the terminator and at the edges of shadow regions for the Marco Polo baseline asteroid, 1999JU3. We also describe the Asteroid Charge Experiment electric field instrumentation intended for Marco Polo. Finally, we find that the differing asteroid and spacecraft potentials on landing could perturb sample collection for the short landing time of 20min that is currently planned.